2020
DOI: 10.1109/access.2020.2995265
|View full text |Cite
|
Sign up to set email alerts
|

A High Frequency Dual Inverted Mesa QCM Sensor Array with Concentric Electrodes

Abstract: Quartz Crystal Microbalance (QCM) is a candidate technology for high sensitivity application. This mass sensor's property depends on the piezoelectric property of the AT-cut quartz crystal. QCM has been widely employed for gas detection due to its comparative advantages including high mass sensitivity, potential for array configuration, low cost, ease of fabrication as well as wide range of available sensitive material compatibility. However, its application has been limited due to two main disadvantages of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This is achieved by studying the direct correlation between change in frequency (Δf) and mass per volume quantity (Δm) [ 50 ] by the application of its sensitivity at the sub mono layer level. Despite its drawbacks [ 51 ] such as violation of the Sauerbrey assumption of adsorption occurring at the rigidity state of samples, QCM has found application in many areas of biomaterials science [ 52 , 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is achieved by studying the direct correlation between change in frequency (Δf) and mass per volume quantity (Δm) [ 50 ] by the application of its sensitivity at the sub mono layer level. Despite its drawbacks [ 51 ] such as violation of the Sauerbrey assumption of adsorption occurring at the rigidity state of samples, QCM has found application in many areas of biomaterials science [ 52 , 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…This wide range of sensitivity enables the measurement of mass changes from micrograms to nanograms. Furthermore, the combination of QCM and sensing films has shown potential for classifying VOCs [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…They compared the influence of electrodes with different sizes on the multi-peak mass sensitivity distribution through theoretical analysis. Aashish et al [ 18 ] and Jiang et al [ 19 ] explored the mass sensitivity distribution of multi-ring electrodes with different proportions based on the finite element method. The investigations have shown that the dot multi-ring electrodes structure can unify the distribution of mass sensitivity.…”
Section: Introductionmentioning
confidence: 99%